Pengembangan Sistem Manajemen Bank Sampah berbasis Web untuk mewujudkan keberhasilan Ekonomi Sirkular di Masyarakat - Utami, Kery; Sandya Prasvita, Desta; Widiastiwi, Yuni (AI Society & STMIK Indonesia, 2023)
This research will be conducted at the Solusi Hijau Main Garbage Bank in the Gunung Sindur District, Bogor Regency. The Solusi Hijau Waste Bank still uses a manual recording system that is easily lost, inefficient, and not dynamic. Therefore it is necessary to make a Web-based Waste Savings Application that can become the main activity facility for the Green Solutions Main Garbage Bank. This application will be used as an interactive interface for Customers and Unit Waste Banks as well as the general public as Prospective Customers or Prospective Management Unit Waste Banks so that they can maximize the performance of the Waste Bank in its development. The Web-based Waste Savings application is a continuation of basic research that has been done before, namely to create digital applications that are utilized by waste banks and the community so that waste banks can become a forum for public education in terms of waste handling and environmental management as well as generating community economic resources. Systems Development Life Cycle (SDLC) is implemented as an Application development method. SDLC is a system development cycle in making waste bank applications by applying the waterfall method. The results of this research in the future are directed to be developed into a standard for Waste Saving System Applications in the community.